Profile of Water Related Diseases in Benue State, Nigeria - Maxwell, Ocheri; Oklo, Ahola; Bernard, Atu (American Journal of Human Ecology, 2012)
The study examines the profile of water related diseases in Benue State from 2000 to 2008.This is done against the backdrop of the intervention effort of governments and organizations in the State with a view to assessing the successes and constraints; analyse the trend and spatial dimension of these diseases in the study area and to suggest appropriate recommendations for management purposes. Data were obtained from Epidemiological Department of the Ministry of Health Makurdi. Simple descriptive statistics was employed in the analyses of the data. The results of analyses showed that cases of water related diseases were recorded in all the LGAs of the state with varied dimension. In order of magnitude of cases studied, malaria ranked the highest, followed by diarrhoea, dysentery, filariasis, onchereriasis, schistosomiasis, typoid and cholera. The study also show a decline in the number of cases of these water related diseases within the period under examination. This probably may be attributed to some intervention by some organizations. Notwithstanding, much is needed as the profile of these diseases is still high in the State. There is need for intensified public enlightenment on personal hygiene, provision of improved water supply in communities where is lacking, and rehabilitation of broken down water infrastructures, water quality survelliance, re-commitment on the part of government and non-governmental organizations in effort to combat water related diseases in the state.